Penerapan Teknologi RO Drip Irrigation dan Nutrisi Presisi untuk Peningkatan Produktivitas Jagung Hibrida - Napsawati Napsawati; Agussalim Agussalim; Asri B (Universitas Pendidikan Nasional, 2026)
Agriculture is a strategic sector in Bantaeng Regency, particularly in the development of hybrid maize. The productivity of maize in the Naik Daun Farmer Group remains low, averaging 0.16 kg per plant, compared to the optimal potential of 0.25–0.33 kg per plant. The main challenges include limited crop management, dependence on rainfall, and conventional fertilization practices. This community service activity aimed to enhance farmers’ capacity through the application of Reverse Osmosis (RO) Drip Irrigation and precision nutrition, using methods such as extension services, field practice mentoring, irrigation system installation, and evaluation of technology adoption.The results showed a significant improvement in farmers’ knowledge and skills; the number of farmers with good understanding increased from 7 (54%) to 13 (100%). Maize productivity increased to 0.28–0.30 kg per plant, approaching the optimal potential, and 88% of farmers were able to implement crop management independently. Thus, the application of RO drip irrigation and precision nutrition has proven effective in improving both productivity and farmer independence, and has the potential to be adapted to other agricultural commodities.